A Dictionary of Space Exploration - Compiled by Dasch, E. Julius (New York Oxford University Press, 2005)
This fascinating and expansive dictionary covers all aspects of space exploration, from A-Train to Zvezda. This jargon-free new edition has been fully revised and updated to take into account the new developments in space exploration on an international scale, with new entries such as Hitomi, Space X Dragon, and Ariane 5 Rocket. All entries are fully cross-referenced for ease of use. In addition, the dictionary also contains links to over 250 space-related websites, and a comprehensive chronology of space exploration.
Keywords: Dictionary